Virulence Genotyping of Pasteurella multocida Isolated from Multiple Hosts from India - Laxmi Narayan Sarangi; Adyasha Priyadarshini; Santosh Kumar; Prasad Thomas; Santosh Kumar Gupta; Viswas Konasagara Nagaleekar; Vijendra Pal Singh (The Scientific World Journal)
In this study, 108 P. multocida isolates recovered from various host animals such as cattle, buffalo, swine, poultry (chicken, duck, and emu) and rabbits were screened for carriage of 8 virulence associated genes. The results revealed some unique information on the prevalence of virulence associated genes among Indian isolates. With the exception of toxA gene, all other virulence associated genes were found to be regularly distributed among host species. Association study between capsule type and virulence genes suggested that pfhA, nanB, and nanH genes were regularly distributed among all serotypes with the exception of CapD, whereas toxA gene was found to be positively associated with CapD and CapA. The frequency of hgbA and nanH genes among swine isolates of Indian origin was found to be less in comparison to its equivalents around the globe. Interestingly, very high prevalence of tbpA gene was observed among poultry, swine, and rabbit isolates. Likewise, very high prevalence of pfhA gene (95.3%) was observed among Indian isolates, irrespective of host species origin.